Distribution pattern of endophytic bacteria and fungi in tea plants - Lin, Haiyan; Liu, Changwei; Peng, Zhong; Tan, Bin; Wang, Kunbo; Liu, Zhonghua (Frontiers in Microbiology, 2022)
Endophytes play important roles in helping plant growth and development. Tea is an economically important crop in China. A good ecological environment will affect the growth of tea and the formation of tea quality. There is a mutually beneficial relationship between plants and endophytes, which can be applied to tea and endophytic microorganisms. However, the distribution pattern and potential functions of endophytic communities in tea trees have not been explained. In this study, two genotypes (BXZ and MF) cultivated under the same conditions were selected, and endophytic bacteria and fungi were analyzed through 16S rRNA and ITS high-throughput sequencing technologies, respectively. The diversity and distribution of endophytic microorganism populations among different tissues were significantly different, which indicated that root > stem > old leaves > new leaves in bacteria, and old leaves> new leaves> roots> stems in fungi. Some endophytic bacterial groups, such as Chryseobacterium, Propionibacterium, Microbacterium, Morganella, etc., could parasitize different tissues, and the average relative abundance of endophytic bacteria was as high as 78%. Some endophytic fungal populations, such as Capnodiales, Pleosporales, and Hypocreales, could also parasitize tea, and the relative abundance accounted for approximately 42.31%-97.41%. The cooperative relationship between endophytic bacteria and fungi in the new leaves was stronger than that in the old leaves, which can better participate in the metabolism of tea material.